Full Genomic Analysis of New Variants of Porcine Reproductive and Respiratory Syndrome Virus Revealed Multiple Recombination Events Between Different Lineages and Sublineages - Wang, Jinglong; Lin, Siyuan; Quan, Dongqun; Wang, Hao; Huang, Jiabin; Wang, Yuxu; Ren, Tongwei; Ouyang, Kang; Chen, Ying; Huang, Weijian; Luo, Tingrong; Wei, Zuzhang (Frontiers in Veterinary Science, 2020)
Porcine reproductive and respiratory syndrome virus (PRRSV) has had a devastating impact on the pig industry in China, and monitoring its genetic diversity is important for epidemiological surveillance and understanding its evolution. Here, we determine the complete genome sequences of two PRRSV strains, GXYL1403 and GXNN1839. Comparative, phylogenetic, and recombination detection program analyses show that the two isolates are recombinant strains with large-fragment amino acid deletions in nsp2. GXYL1403 possesses a unique deletion region of 124 amino acids in nsp2, and GXNN1839 contains a deletion of 131 amino acids in nsp2 as compared with VR2332. Further analysis of the full-length sequence suggests that GXYL1403 is a natural recombinant between sublineages 8.1 (CH-1a like) and 8.3 (JXA1-like). The recombination site of GXYL1403 is located in nsp9–nsp12 (8961nt−11181nt). GXNN1839 is a natural recombinant between the lineage 5 (VR-2332-like) and lineage 1 (NADC30-like) strains. The recombination events occurred in nsp9 (7872nt-8162nt) and in ORF2 (12587nt−13282nt) in the genome of GXNN1839. These results provide new evidence that PRRSV strains circulating in the environment have undergone recombination among the different lineages or sublineages of field strains, and these add to our understanding of RNA combination events that occur in PRRSV.